2022
DOI: 10.1111/ddi.13607
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and drivers of the global diversity of non‐native macrofungi

Abstract: Aim: To uncover the biogeography of non-native macrofungal diversity worldwide, by analysing patterns and drivers of (1) regional variation in species richness, (2) compositional similarity between regional species assemblages and (3) the spatiotemporal trends of first records. Location: Global.Methods: We used a database providing 1608 distribution records of 554 non-native macrofungal species in 167 national and sub-national regions worldwide. Regression models accounting for regional levels of recording cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 96 publications
1
7
1
Order By: Relevance
“…We note that large numbers of non-native mushroom species may be present (e.g. 87% of Hawaiian mushrooms in our study), further challenging comparisons Monteiro et al (2022). recently found that islands do not necessarily have more non-native mushrooms than mainlands, but certain regions, including Oceania, have higher species richness of non-native mushroom species.…”
contrasting
confidence: 67%
See 1 more Smart Citation
“…We note that large numbers of non-native mushroom species may be present (e.g. 87% of Hawaiian mushrooms in our study), further challenging comparisons Monteiro et al (2022). recently found that islands do not necessarily have more non-native mushrooms than mainlands, but certain regions, including Oceania, have higher species richness of non-native mushroom species.…”
contrasting
confidence: 67%
“…87% of Hawaiian mushrooms in our study), further challenging comparisons. Monteiro et al (2022) recently found that islands do not necessarily have more non‐native mushrooms than mainlands, but certain regions, including Oceania, have higher species richness of non‐native mushroom species. Finally, datasets that include only soils may exclude large groups of mushrooms, including lignicolous species.…”
Section: Discussionmentioning
confidence: 99%
“…However, we also found that, for the time being, a large percentage of checklist authors still have limited knowledge of this terminology. For example, significant positive relationships between taxonomic expertise and levels of terminology knowledge were found for plants, vertebrates, and invertebrates, but not for fungi and microorganisms groups for which knowledge about invasions is difficult to obtain and remains limited (Litchman, 2010; Monteiro et al, 2022). Thus, efforts to improve knowledge of this terminology and its harmonized adoption among checklist authors seem justified.…”
Section: Discussionmentioning
confidence: 99%
“…Alien richness hotspots of macrofungal (i.e. of those that form visible fruiting bodies) saprobes and ectomycorrhiza were found in Europe, the Americas and Oceania (Monteiro et al, 2020(Monteiro et al, , 2022. However, biogeographic patterns of fungal guilds can differ substantially (Põlme et al, 2020;Tedersoo et al, 2014) and a similar global analysis for alien fungal pathogens is missing to date, despite their environmental and socio-economic impacts.…”
Section: Main Conclusionmentioning
confidence: 99%